2015
DOI: 10.1063/1.4913304
|View full text |Cite
|
Sign up to set email alerts
|

Heavy fermion Ce3Co4Sn13 compound under pressure

Abstract: The non-magnetic heavy fermion compound Ce 3 Co 4 Sn 13 was studied under pressure. We report single crystalline measurements of electrical resistivity as a function of temperature q(T) under pressure. Some characteristic features related to a structural transition (T S ), crystalline field effects (T CEF ), and a low temperature maximum (T max ), possibly connected simultaneously to the onset of Kondo lattice coherence and short range magnetic correlations, were identified in the q(T) data. A pressure-tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Upon cooling, a sudden increase in the resistivity is observed at T CDW = 279 K for La 3 Cd 2 As 6 and at T CDW = 136 K for Ce 3 Cd 2 As 6 . Below T CDW , the observed semiconducting behavior indicates the opening of an energy gap due to the CDW phase transition, similar to Sr 3 Ir 4 Sn 13 , Ca 3 Ir 4 Sn 13 , Ce 3 Co 4 Sn 13 , and La 3 Co 4 Sn 13 . Notably, the resistivity of La 3 Cd 2 As 6 increases up to 10 10 Ω cm at 12 K, as presented in the inset of Figure a. This large increase of 13 orders of magnitude is a rare property in narrow-gap semiconductors, which are typically prone to impurity bands that may dominate the electronic properties at low temperatures. , Remarkably, this increase was achieved in the as-grown single crystal, which suggests that sample quality could be improved through further purification.…”
Section: Resultsmentioning
confidence: 89%
“…Upon cooling, a sudden increase in the resistivity is observed at T CDW = 279 K for La 3 Cd 2 As 6 and at T CDW = 136 K for Ce 3 Cd 2 As 6 . Below T CDW , the observed semiconducting behavior indicates the opening of an energy gap due to the CDW phase transition, similar to Sr 3 Ir 4 Sn 13 , Ca 3 Ir 4 Sn 13 , Ce 3 Co 4 Sn 13 , and La 3 Co 4 Sn 13 . Notably, the resistivity of La 3 Cd 2 As 6 increases up to 10 10 Ω cm at 12 K, as presented in the inset of Figure a. This large increase of 13 orders of magnitude is a rare property in narrow-gap semiconductors, which are typically prone to impurity bands that may dominate the electronic properties at low temperatures. , Remarkably, this increase was achieved in the as-grown single crystal, which suggests that sample quality could be improved through further purification.…”
Section: Resultsmentioning
confidence: 89%
“…Upon cooling, a sudden increase in the resistivity is observed at T CDW = 279 K for La3Cd2As6 and at T CDW = 136 K for Ce 3 Cd 2 As 6 . Below T CDW , the observed semiconducting behavior indicates the opening of an energy gap due to the CDW phase transition, similar to Sr 3 Ir 4 Sn 13 , Ca 3 Ir 4 Sn 13 36 , Ce 3 Co 4 Sn 13 and La 3 Co 4 Sn 13 [37][38][39][40] . Notably, the resistivity of La 3 Cd 2 As 6 increases up to 10 10 Ω cm at 12 K, as presented in the inset of Fig.…”
Section: Resultsmentioning
confidence: 75%
“…For example, (Ca, Sr) 3 Ir 4 Sn 13 exhibit charged density wave order at T = 33 K and 138 K respectively and the transition temperature can be suppressed by chemical or physical pressure to drive the system close to a quantum critical point [12,11]. Another interesting stannide based compound is Ce 3 Co 4 Sn 13 which shows complicated semiconducting property and exhibits single channel single ion impurity Kondo effect with T K (Kondo temperature) = 1.5 K [13,14]. Based on structural, magnetic, and electrical transport properties, it is observed that the Pr containing compounds crystallize in cubic structure with 3+ ionic state with no magnetic ordering and presence of crystalline electric field excitations.…”
Section: Introductionmentioning
confidence: 99%